2018
DOI: 10.1155/2018/3946862
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability and Feasibility of Integrating Point-of-Care Diagnostic Testing of Sexually Transmitted Infections into a South African Antenatal Care Program for HIV-Infected Pregnant Women

Abstract: Background Chlamydia trachomatis (CT), Neisseria gonorrhoeae (NG), and Trichomonas vaginalis (TV) infections may increase the risk of vertical transmission of the human immunodeficiency virus (HIV). In resource-limited settings, symptomatic screening, and syndromic management of sexually transmitted infections (STIs) during pregnancy continue to be the standard of care. In the absence of diagnostic testing, asymptomatic infections in pregnant women go untreated. Objective To describe the acceptability and fea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(69 citation statements)
references
References 16 publications
1
68
0
Order By: Relevance
“…Several studies have shown that this can be used in settings with basic laboratory infrastructure. The utility of GeneXpert has been evaluated in remote populations such as an aboriginal community in Australia ; in routine antenatal care in Papua New Guinea (with STI rates by GeneXpert of CT 20%, NG 11.2% and TV 37.6%) ; in HIV‐infected pregnant women in South Africa (40.2% with STIs) . Another utility study in South Africa in HIV‐negative women presenting for STI care or with symptoms (CT 18.4%, NG 5.2%, TV 3%) resulted in STI testing of symptomatic and asymptomatic women and the same‐day treatment, with expedited partner treatment and reduced reinfection after six months .…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have shown that this can be used in settings with basic laboratory infrastructure. The utility of GeneXpert has been evaluated in remote populations such as an aboriginal community in Australia ; in routine antenatal care in Papua New Guinea (with STI rates by GeneXpert of CT 20%, NG 11.2% and TV 37.6%) ; in HIV‐infected pregnant women in South Africa (40.2% with STIs) . Another utility study in South Africa in HIV‐negative women presenting for STI care or with symptoms (CT 18.4%, NG 5.2%, TV 3%) resulted in STI testing of symptomatic and asymptomatic women and the same‐day treatment, with expedited partner treatment and reduced reinfection after six months .…”
Section: Resultsmentioning
confidence: 99%
“…7,14 Briefly, we incorporated same-day point-of-care diagnostic testing and treatment for urogenital CT, NG and TV infections into routine antenatal care provided to HIV-infected pregnant women. 14 We found antenatal STI screening to be highly acceptable to women and feasible. Participants who tested positive for CT, NG and/or TV during their antenatal care visit were treated and invited for repeat testing 21 days later.…”
Section: Methodsmentioning
confidence: 99%
“…Participants self-collected vaginal swab specimens using Xpert V R CT/NG Vaginal/Endocervical Specimen Collection kits (Cepheid, Sunnyvale, California, USA) as previously described. 14 Trained staff at each clinic tested swabs for CT, NG and TV per the manufacturer's instructions (Xpert V R CT/NG and Xpert V R TV assays, Cepheid, Sunnyvale, California, USA). The Xpert V R assays have greater than 99% sensitivity and specificity for the organisms tested.…”
Section: Specimen Collection Testing and Managementmentioning
confidence: 99%
“…Two TPPs have been developed for NG POCT in resource-constrained settings; the first (TPP1) for a test for etiological diagnosis of NG and CT, and the second (TPP2) for the detection of NG AMR determinants that can predict resistance/susceptibility to existing and upcoming antibiotics. Novel technologies for NG detection and AMR prediction are being developed and it is important to ensure they meet the needs of end users particularly in resource-constrained settings [36,45,46].…”
Section: Gonorrhoea a Priority Pathogen In The Era Of Antimicrobial mentioning
confidence: 99%